2010
DOI: 10.1029/2010ja015713
|View full text |Cite
|
Sign up to set email alerts
|

Features of separatrix regions in magnetic reconnection: Comparison of 2‐D particle‐in‐cell simulations and Cluster observations

Abstract: [1] In collisionless magnetic reconnection, the in-plane Hall currents are carried mainly by the magnetized electrons. The in-plane Hall currents are directed toward the X line along the magnetic field lines just inside the separatrices and away from the X line along the separatrices. Such a current system leads to the quadrupole out-of-plane magnetic field with the peaks between the regions carrying the in-plane currents. Simultaneously, the electron flow toward the X line along the separatrices causes electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
107
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 97 publications
(128 citation statements)
references
References 36 publications
13
107
0
7
Order By: Relevance
“…The current in the reconnection plane is dominated by electron motion [32]. In anti-parallel magnetic reconnection, electrons stream along the separatrices from the strong magnetic field region into the X-line region where electrons are accelerated by the reconnection electric field.…”
Section: Characteristics Of the Reconnection Diffusion Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current in the reconnection plane is dominated by electron motion [32]. In anti-parallel magnetic reconnection, electrons stream along the separatrices from the strong magnetic field region into the X-line region where electrons are accelerated by the reconnection electric field.…”
Section: Characteristics Of the Reconnection Diffusion Regionmentioning
confidence: 99%
“…In anti-parallel magnetic reconnection, electrons stream along the separatrices from the strong magnetic field region into the X-line region where electrons are accelerated by the reconnection electric field. The accelerated electrons flow out along the magnetic field lines on the inside of the separatrices [21,32]. Thus, a current system is formed that streams out along the separatrices and flows into the X-line along these magnetic field lines inside the separatrices [23,32].…”
Section: Characteristics Of the Reconnection Diffusion Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Separatrices are thin boundary layers between plasmas with different properties (density, temperature, and flow pattern) [1][2][3] and subject to instabilities, wave activity and turbulence [4][5][6]. One of the distinctive features of collisionless magnetic reconnection is the formation of localized low density regions along the separatrices [7,8]. These depletion areas are called cavities.…”
Section: Introductionmentioning
confidence: 99%
“…On the same field lines, higher energy electrons have also been reported to be directed away from the diffusion region Nagai et al, 2001;Wang et al, 2010a). Such a configuration has also been confirmed by Lu et al (2010) who showed that the electron density depletions formed along the separatrices are outside the peaks of the out-of-plane magnetic field.…”
Section: Introductionmentioning
confidence: 53%